THE LAYER HEIGHT VARIATIONS EFFECT ON TENSILE STRENGTH OF 3D PRINTING PRODUCT PLA MATERIAL BASED - Sally Cahyati; Yusuf Al Furqon (Jurnal Rekayasa Mesin, 2022)
3D Printing products are produced and used for many purposes like biomedical equipment, mechanical part, and so on. Therefore, mechanical properties are important for 3D Printing products.  Layer height as one of the 3D Printing process parameters will be observed to know the effect on product tensile strength and printing time. The research has used ASTM D638 standard specimens from PLA material base with layer height parameter variations between 0.1mm, and 0.3 mm. The specimens are printed by 3D Print Creality Ender 3-Pro, then will be tested by Tensile Machine. The result finds both the printing time and the tensile strength of 3D printing products are affected by the variations in the layer height. The printing time will decrease along with the layer height increasing. For the layer height dimension nearly the nozzle diameter of 0.3 mm, the tensile strength is 10.16 MPa. It is significantly better than the 0.1 mm to 0.25 mm layer height which has a tensile strength range of 7.07 to 8.59 MPa. The condition is because the path internal bond in the 0.3 mm layer height has more homogeneity.